Intentional poisoning among preadolescents at one poison center in Saudi Arabia - Q, Menyfah; -, Alanazi; Salam, Mahmoud (Indian Journal of Child Health, 2016)
Background: The epidemiology of intentional poisoning among preadolescents in conservative communities needs further exploration. Preadolescence (9-14 years) is a remarkable human developmental stage with a heightened risk for such incidents, often less discussed than adolescence. Objective: To present a report on intentional poisoning incidents among preadolescents visiting a single poison center in Saudi Arabia. Materials and Methods: A chart review of 315 poisoning reports was conducted between 2009 and 2011. It was followed by a phone interview of parents of poisoned children to investigate the demographic, incident and outcome characteristics. Cases of accidental and chronic poisoning were excluded. Results: Nine eligible cases were identified (2.9%); four were classified as suicidal attempts, two nonsuicidal self-injurious, and three were unknown. Of the five males and four females, three had chronic medical conditions (G6PD deficiency, epilepsy, or asthma) while six were previously healthy. Seven cases ingested medications (acetaminophen, desmopressin, augmentin and benylin, amitriptyline, and chlordiazepoxide) while two ingested clorox, all in large doses. Conclusions: Few intentional poisoning incidents were observed among Saudi preadolescents, which could be an underreported figure in a culturally and religiously conservative community.